POS0135 REDUCING IMMUNOGENICITY OF PEGLOTICASE (RECIPE) WITH CONCOMITANT USE OF MYCOPHENOLATE MOFETIL IN PATIENTS WITH REFRACTORY GOUT: A PHASE II RANDOMIZED CONTROLLED TRIAL - Khanna, P.; Khanna, D.; Cutter, G.; Foster, J.; Melnick, J.; Jaafar, S.; Biggers, S.; Rahman, F.; Kuo, H.C.; Feese, M.; Saag, K. (Annals of the rheumatic diseases, 2021)
Pegloticase is a recombinant, pegylated uricase, used for treatment of gout patients who fail oral urate lowering therapy (ULT). Its use has been limited due to immunogenicity leading to infusion reactions.1 We evaluated if co-administration of an immunomodulatory agent could prolong the efficacy of pegloticase. Participants were recruited in a Phase II, double-blind, placebo-controlled trial over 18 months and randomized in a 3:1 ratio by site. Inclusion criteria were: a) Age ≥ 18 years who met 2015 ACR/EULAR gout classification criteria and b) chronic refractory gout defined as symptoms inadequately controlled with ULT or contraindications. After a 2-week run-in of mycophenolate mofetil (MMF) 1000 mg twice daily or matching placebo (PBO), they received a combination of pegloticase 8 mg biweekly with MMF or PBO for 12 weeks. Subsequent to this MMF or PBO were discontinued but pegloticase was continued for another 12 weeks. The primary endpoint was proportion of patients who sustained a serum urate (SU) level of ≤ 6 mg/dl at 12 weeks. Secondary endpoints included 24-week durability of SU ≤ 6 mg/dl and rate of adverse events (AEs). Fisher's exact test and Wilcoxon two-sample test were used for analyses along with Kaplan-Meier estimates and log-rank tests to compare survival curves between groups. Hypothesis tests were two-tailed and p-value (p) < 0.05 indicated statistical significance. Of 42 subjects screened, 35 were randomized, and 32 who received at least one dose of pegloticase were included in modified intention to treat analyses. Subjects were predominantly men (88%), mean age of 55.2 years (SD=9.7). Mean duration of gout was 13.4 years (SD=9.0), mean baseline sUA was 9.2 mg/dL (SD=1.6). Tophi were present in 88% and majority were on optimized ULT - 59% on allopurinol and 16% on febuxostat, with 63% reporting > 1 flare in the past year. At baseline both arms (MMF vs. PBO) had similar comorbidities – (82% vs 70%), diabetes mellitus/metabolic syndrome (14% vs 20%), coronary artery disease/peripheral vascular disease (41% vs.70%), BMI>30 (86% vs. 90%) and renal insufficiency (defined as eGFR < 90 mL/min; 73% vs. 70%). At 12 weeks, 19 of 22 (86%) in the MMF arm achieved SU ≤ 6 mg/dl compared to 4 of 10 (40%) in PBO arm (p-value = 0.01). At 24 weeks, the SU was ≤ 6 mg/dl in 68% of MMF arm vs. 30% in PBO (p-value = 0.06), and rates of AEs per month were similar between groups with the PBO arm having more infusion reactions (30% vs. 0%). The MMF arm had higher AEs compared to placebo: musculoskeletal (41% vs. 10%), gastrointestinal (18% vs. 10%), and infections (9% vs. 0%). Figure 1 shows that the percentage of subjects maintaining a sUA < 6 mg/dL at 12 weeks was significantly higher (p=0.02) in the MMF arm, and a significant difference (p=0.03) at 24 weeks indicates sustained benefit from MMF. To our knowledge this is the first randomized-controlled proof of concept trial to demonstrate the ability of an immunomodulatory agent in prolonging the efficacy of pegloticase. Short-term concomitant use of MMF therapy with pegloticase was well tolerated and showed a clinically meaningful improvement in the targeted SU ≤6 mg/dL at 12 and 24 weeks. This study suggests an innovative approach to utilize pegloticase therapy in patients with chronic gout. [1]Sundy et al. Efficacy and tolerability of pegloticase for the treatment of chronic gout in patients refractory to conventional treatment: two randomized controlled trials. JAMA. 2011;306(7):711-20. Puja Khanna Consultant of: Horizon Pharmaceuticals, Swedish Orphan Biovitrum A, Grant/research support from: Selecta, 2)DYVE, Dinesh Khanna Consultant of: Horizon Pharmaceuticals, Gary Cutter: None declared, Jeff Foster: None declared, Josh Melnick: None declared, Sara Jaafar: None declared, Stephanie Biggers: None declared, Fazlur Rahman: None declared, Hui-Chen Kuo: None declared, Michelle Feese: None declared, Kenneth Saag Consultant of: AbbVie, Inc., Bayer, Daiichi Sankyo Company LTD, Gilead Services, Inc., Horizon Pharma plc, Mallinkrodt, Radius Health, Inc., Roche/Genentech, Shanton Pharma Co., LTD, Teijin, Dyve Bioscience, LG Chem, Regeneron Pharmaceuticals., Swedish Orphan Biovitrum AB, Takeda Pharmaceuticals America, Inc., [Display omitted]